Mitochondrial Dynamics and Mitochondria-Lysosome Contacts in Neurogenetic Diseases - Pijuan, Jordi; Cantarero, Lara; Natera-de Benito, Daniel; Altimir, Arola; Altisent-Huguet, Anna; Díaz-Osorio, Yaiza; Carrera-García, Laura; Expósito-Escudero, Jessica; Ortez, Carlos; Nascimento, Andrés; Hoenicka, Janet; Palau, Francesc (Frontiers in Neuroscience, 2022)
Mitochondrial network is constantly in a dynamic and regulated balance of fusion and fission processes, which is known as mitochondrial dynamics. Mitochondria make physical contacts with almost every other membrane in the cell thus impacting cellular functions. Mutations in mitochondrial dynamics genes are known to cause neurogenetic diseases. To better understand the consequences on the cellular phenotype and pathophysiology of neurogenetic diseases associated with defective mitochondrial dynamics, we have compared the fibroblasts phenotypes of (i) patients carrying pathogenic variants in genes involved in mitochondrial dynamics such as DRP1 (also known as DNM1L), GDAP1, OPA1 and MFN2, and (ii) patients carrying mutated genes that their dysfunction affects mitochondria or induces a mitochondrial phenotype, but that are not directly involved in mitochondrial dynamic network, such as FXN (encoding frataxin, located in the mitochondrial matrix), MED13 (hyperfision phenotype) and CHKB (enlarged mitochondria phenotype). We identified mitochondrial network alterations in all patients’ fibroblasts except for CHKBQ198*/Q198*. Functionally, all fibroblasts showed mitochondrial oxidative stress, without membrane potential abnormalities. The lysosomal area and distribution were abnormal in GDAP1W67L/W67L, DRP1K75E/+, OPA1F570L/+ and FXNR165C/GAA fibroblasts. These lysosomal alterations correlated with mitochondria-lysosome membrane contact sites (MCSs) defects in GDAP1W67L/W67L exclusively. The study of mitochondrial contacts in all samples further revealed a significant decrease in MFN2R104W/+ fibroblasts. GDAP1 and MFN2 are outer mitochondrial membrane (OMM) proteins and both are related to Charcot-Marie Tooth neuropathy. Here we identified their constitutive interaction as well as MFN2 interaction with LAMP-1. Therefore MFN2 is a new mitochondria-lysosome MCSs protein. Interestingly, GDAP1W67L/W67L and MFN2R104W/+ fibroblasts carry pathogenic changes that occur in their catalytic domains thus suggesting a functional role of GDAP1 and MFN2 in mitochondria–lysosome MCSs. Finally, we observed starvation-induced autophagy alterations in DRP1K75E/+, GDAP1W67L/W67L, OPA1F570L/+, MFN2R104W/+ and CHKBQ198*/Q198* fibroblasts. These genes are related to mitochondrial membrane structure or lipid composition, which would associate the OMM with starvation-induced autophagy. In conclusion, the study of mitochondrial dynamics and mitochondria-lysosome axis in a group of patients with different neurogenetic diseases has deciphered common and unique cellular phenotypes of degrading and non-degrading pathways that shed light on pathophysiological events, new biomarkers and pharmacological targets for these disorders.